The Black Church : this is our story, this is our song [videorecording (DVD)] - Gates, Henry Louis, Jr; Winfrey, Oprah; West, Cornel; Pierce, Yolanda Nicole; Sharpton, Al; Rossi, Antonio (Cinematographer); Smith, Graham (Cinematographer); Head, Matthew, 1982- (PBS, 2021)
"Chronicles the rich history of an institution at the heart of the African American experience. Beginning with enslavement, traveling through Emancipation, Jim Crow, the Great Migration, the Civil Rights movement, and ending in the present-day, Gates takes viewers on a journey through time, focusing on the key events, charismatic figures, political debates, and musical traditions that have shaped, and been shaped by, the Black Church. The series also explores the complexity of these spaces of worship at a time when many believe it is at a crossroads. A chorus of leading scholars, ministers, and cultural influencers who grew up in the Black Church will weigh in and give meaning to events past and present."--Container